Physico-chemical characterisation of sago starch - Fasihuddin B., Ahmad; Peter A., Williams; Jean-Louis, Doublier; Sylvie, Durand; Alain, Buleon (Elsevier, 1999)
The physico-chemical characteristics of various sago starch samples from South East Asia were determined and compared to starches from other sources. X-ray diffraction studies showed that all the sago starches exhibited a C-type diffraction pattern. Scanning electron microscopy showed that they consist of oval granules with an average diameter around 30 μm. Proximate composition studies showed that the moisture content in the sago samples varied between 10.6% and 20.0%, ash between 0.06% and 0.43%, crude fat between 0.10% and 0.13%, fiber between 0.26% and 0.32% and crude protein between 0.19% and 0.25%. The amylose content varied between 24% and 31%. The percentage of amylose obtained by colourimetric determination agreed well with the values obtained by fractionation procedures and potentiometric titration. Intrinsic viscosities and weight average molecular weight were determined in 1M KOH. Intrinsic viscosity for amylose from sago starches varied between 310 and 460 ml/g while for amylopectin the values varied between 210 and 250 ml/g. The molecular weight for amylose was found to be in the range of 1.41×106 to 2.23×106 while for amylopectin it was in the range of 6.70×106 to 9.23×106. The gelatinisation temperature for the sago starches studied varied between 69.4°C and 70.1°C. The exponent ‘a’ in the Mark–Houwink equation and the exponent ‘α’ in the equation Rg=kMα was found to be 0.80 and 0.58, respectively for amylose separated from sago starch and these are indicative of a random coil conformation. Two types of pasting properties were observed. The first was characterised by a maximum consistency immediately followed by sharp decrease in consistency while the second type was characterised by a plateau when the maximum consistency was reached.